Contact with mentally ill people Does it effect nurses' attitude toward mental illness? - Khaleghparast Athari Sh (Iran University of Medical Sciences, 1999)
B a c kgro u n d: Contact theory has been mentioned for years. Can it effect peoples' attitude a question to be answered. Objective: To determine nurses' attitude toward mental illness with different levels of contact with mentally ill people. Design: This was a correlational study. Using a two part questionnair data were collected about contact level and attitude of a group of nurses. Sample: Four hundred nurses from both sexes were randomly selected from Tehran, Iran and Shahid Beheshti universities. Result: There was a negative relation between the level of contact of nurses with mentally ill and their attitude toward mental illness (p=O.OOO,Gamma coeficient= -- 0.47). Conclusion: Attitude of nurses should be considered as an important factor in caring for mentally ill people. further researches are recommended on factors effecting their attitude.,